Coupling and Coordination of the Regional Economy, Tourism Industry, and Exhibition Industry of China’s Provinces - Mengyuan Lu (Discrete Dynamics in Nature and Society)
There is a close correlation between regional economy, tourism, and exhibition industry. By constructing a system of evaluation indicators for the regional economy, tourism industry, and exhibition industry, the coupled coordination degree model was used to calculate the degree of synergy of the regional economy, tourism industry, and exhibition industry in China from 2013 to 2019. In addition, the influencing factors of the degree of synergy were analyzed by gray correlation analysis. As shown by the results, the comprehensive development scores of regional economy, tourism industry, and exhibition industry show an overall growth trend, while the development level index presents a spatial distribution pattern of decreasing gradient from coastal area to inland in space. Apart from that, the integration and development of regional economy, tourism industry, and exhibition industry show a continuous coordinated and benign development. On a national scale, the degree of integration of the regional economy-tourism industry-exhibition industry in China has gradually developed and improved from bare coordination to good coordination. Besides, the degree of coupling and coordination of regional economy-tourism-exhibition industry varies greatly among provinces. Moreover, all the indexes have a strong impact on the coupling and coordination degree of the regional economy-tourism industry-exhibition industry. Compared with the exhibition industry system, the economic system and tourism system have a stronger impact on the coupling and coordination degree of the regional economy-tourism industry-exhibition industry.